2021
DOI: 10.1097/won.0000000000000796
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Related Factors Associated With Stoma and Peristomal Complications Following Fecal Ostomy Surgery

Abstract: PURPOSE:Ostomy creation is often an integral part of the surgical management of various diseases including colorectal malignancies and inflammatory bowel disease. Stoma and peristomal complications may occur in up to 70% of patients following ostomy surgery. The aim of this scoping literature review was to synthesize evidence on the risk factors for developing complications following creation of a fecal ostomy. DESIGN: Scoping literature review. SEARCH STRATEGY: Two independent researchers completed a search o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 85 publications
1
36
0
Order By: Relevance
“…A review reported by Zelga et al found that age over 65 years, female sex, BMI higher than 25 kg/m 2 , diabetes mellitus, abdominal malignancy, and lack of perioperative stoma site marking are risk factors associated with increased likelihood of stoma-related complications. 46 Our results showed a mean age of 64.5 years and the presence of diabetes in 18.4% of cases.…”
Section: Discussionmentioning
confidence: 45%
“…A review reported by Zelga et al found that age over 65 years, female sex, BMI higher than 25 kg/m 2 , diabetes mellitus, abdominal malignancy, and lack of perioperative stoma site marking are risk factors associated with increased likelihood of stoma-related complications. 46 Our results showed a mean age of 64.5 years and the presence of diabetes in 18.4% of cases.…”
Section: Discussionmentioning
confidence: 45%
“…Findings from multiple studies also suggest that patients living with an ostomy are more likely to experience peristomal irritant contact dermatitis due to exposure of the skin to fecal effluent. 42,46,53 Significant differences were not found when the OST score was analyzed based on time since ostomy surgery, preoperative stoma site marking, and presence of a retracted ostomy. Considered collectively, these do not allow firm conclusions concerning the discriminant validity of the adapted OST.…”
Section: Discussionmentioning
confidence: 96%
“…A scoping literature review by Zelga and colleagues found that diabetes is one of five independent risk factors associated with an increased risk of stomal or peristomal complications. 24 Patients who have this disease need special instructions about appropriate dietary intake while maintaining adequate blood glucose control. The optimal diet is achieved through a combination of education, monitoring and revising care plans, and individualizing the plan to specific told to expect some cramping and discomfort during digital manipulation.…”
Section: Nutritionmentioning
confidence: 99%